The dynamics of organizational culture in the private, government, and semi-government companies in Poland - Habte Woldu; Magdalena Biederman (Journal for East European Management Studies, 1999)
This paper examines the dynamics of culture in Poland in three phases by measuring multilevel cultural dimensions. The first phase examines cultural changes over time, the second phase looks at cultural dynamics by comparing Polish respondents with those of USA and Russia, and the third phase looks into organizational cultural dynamics by analyzing respondents in five types of Polish business organizations. The business organizations include government, semi government, and cooperatives, domestic private and foreign owned companies (joint ventures and wholly owned companies). The study found that there are cultural dynamics within certain demographic groups and the five different Polish business organizations, however the dynamics are still most strongly influenced by the preexisting national cultural backgrounds. – – In dieser Arbeit wird mit Hilfe einer Betrachtung vielschichtiger kultureller Dimensionen die Dynamik der polnischen Kultur in drei Schritten untersucht. Der erste Schritt widmet sich den kulturellen Veränderungen im Laufe der Zeit. Im zweiten Schritt wird die kulturelle Dynamik vor dem Horizont eines Vergleichs von polnischen Befragten mit US-amerikanischen und russischen Befragten betrachtet. Im dritten Schritt nun wird die organisatorische und kulturelle Dynamik anhand einer Analyse von Befragten aus fünf verschiedenartigen polnischen Unternehmen betrachtet. Zu diesen Unternehmenstypen gehören staatliche und halbstaatliche Unternehmen, genossenschaftliche Unternehmen und Privatunternehmen mit polnischem oder ausländischem Eigentümer. Das Ergebnis der Studie zeigt, daß es innerhalb bestimmter demographischer Gruppen und innerhalb der fünf polnischen Unternehmenstypen kulturelle Dynamik gibt. Diese Dynamik ist jedoch noch immer stark von alten nationalen kulturellen Hintergründen bestimmt.
Keywords: 650